Additively manufactured implant components for imaging validation studies. (July 2018) - Van de Kleut, Madeleine L; Yuan, Xunhua; Athwal, George S; Teeter, Matthew G
Radiographic imaging is the current standard for evaluating postoperative joint replacements. Prior to application, such imaging methods need to be validated to determine the lower limits of performance under ideal conditions, using either a phantom or cadaver setup. Conventionally manufactured orthopedic implants for use in such studies are not always accessible and may be cost-prohibitive to purchase. We propose the use of additively manufactured implants as a cheaper, more accessible alternative for use in radiographic imaging validation studies. Bias and repeatability were compared between conventionally manufactured and additively manufactured reverse total shoulder implant sets under a standard model-based radiostereometric analysis phantom study environment. Measurements were compared using the humeral stem or glenosphere model relative to reference bone beads, and the humeral stem relative to the glenosphere model to measure implant relative displacement. Compared to the conventionally manufactured implants, the additively manufactured implants had less bias along the internal–external rotation axis (p < 0.001), but greater bias along the abduction–adduction and flexion–extension rotation axes (p = 0.005, 0.011). Additively manufactured implants had greater repeatability along the internal–external rotation axis (p < 0.001), but worse repeatability along the medial–lateral translation axis (p = 0.001) and the abduction–adduction rotation axis (p < 0.001). Differences were on the orders of 0.01 mm and 0.5°. For the purpose of validating two-dimensional–three-dimensional radiographic imaging techniques of orthopedic implants, additively manufactured implants can be used in place of conventionally manufactured implants, assuming they are fabricated to the manufacturer's specifications. Observed differences were within the errors of the measurement technique and not clinically meaningful.